Growth and inequality in the distribution of India's consumption expenditure 1983 to 2009-10 - S. Subramanian; D. Jayaraj (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper undertakes an assessment of the evolution of inequality in the distribution of consumption expenditure in India over the last quarter-century, from 1983 to 2009-10, employing data available in the quinquennial 'thick' surveys of the National Sample Survey Office. We find that plausible adjustments to the data, along with an emphasis on 'centrist' rather than 'rightist' or 'leftist' inequality measures, lead to a picture of inequality in the distribution of consumption expenditure widening over time, which is at odds with the impression of more or less unchanging inequality conveyed in some of the literature available on the subject in India.
Keywords: D30; D31; O15; O40; 330; absolute inequality; relative inequality; intermediate inequality; coefficient of variation; standard deviation; Krtscha measure